Cholestatic jaundice caused by cloxacillin: macrophage inhibition factor test in preventing rechallenge with hepatotoxic drugs. Issue 6219 (5th April 1980) - Enat, R; Pollack, S; Ben-Arieh, Y; Livni, E; Barzilai, D
Abstract : Severe intrahepatic cholestasis occurred in a patient after taking nitrofurantoin, ampicillin, and cloxacillin. As only nitrofurantoin was known to cause cholestasis she was given cloxacillin again two years later. The cholestasis reappeared at once. A macrophage inhibition factor test confirmed that cloxacillin was the offending drug. Cloxacillin should be added to the growing list of drugs causing cholestasis. Inadvertent rechallenge with hepatototoxic drugs might be prevented by routine use of the macrophage inhibition factor test.